Juridical Analysis of The Application of Penalties For Perpetrators of Narcotics Crimes - Depari, Jon Heder; Aspan, Henry; Zarzani, Riza (Fakultas Hukum Dehasen, 2026)
The purpose of this writing is to find out the Implementation of Criminal Law for Narcotics Crime Offenders and the legal status of the use of Narcotics in Law Number 35 of 2009 concerning Narcotics. By using the normative legal research method. Criminal Law for Narcotics Crime Offenders According to Law Number 35 of 2009 In the Article there is a minimum criminal threat of 4 (four) years. Legal Status Against the Use of Narcotics in Law Number 35 of 2009 concerning Narcotics, namely the criminal provisions contained in Law Number 35 of 2009 concerning Narcotics are formulated in Chapter XV Criminal Provisions Articles 111 to Article 148.